2000
DOI: 10.1128/iai.68.7.4349-4353.2000
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Activity of a Nontoxic Mutant ofEscherichia coliHeat-Labile Enterotoxin on Systemic and Mucosal Immune Responses Elicited against a Heterologous Antigen Carried by a LiveSalmonella entericaSerovar Typhimurium Vaccine Strain

Abstract: Systemic and mucosal antibody responses against both the major subunit of colonization factor antigen I (CFA/I) of enterotoxigenic Escherichia coli (ETEC) and the somatic lipopolysaccharide expressed by recombinant bivalent Salmonella vaccine strains were significantly enhanced by coadministration of a detoxified derivative with preserved adjuvant effects of the ETEC heat-labile toxin, LT (R192G) . The results further support the adjuvant effects of LT (R192G) and represent a simple alternative to improve resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 32 publications
0
15
0
3
Order By: Relevance
“…Derivatives of CT and LT have been explored as adjuvants in the development of Helicobacter pylori vaccines (24). Previous studies have also shown that immune responses to a bivalent Salmonella vaccine expressing the ETEC colonization factor CFA/I were enhanced by the coadministration of a mutant LT that was used as a mucosal adjuvant (16).…”
Section: Discussionmentioning
confidence: 99%
“…Derivatives of CT and LT have been explored as adjuvants in the development of Helicobacter pylori vaccines (24). Previous studies have also shown that immune responses to a bivalent Salmonella vaccine expressing the ETEC colonization factor CFA/I were enhanced by the coadministration of a mutant LT that was used as a mucosal adjuvant (16).…”
Section: Discussionmentioning
confidence: 99%
“…LT and cholera toxin are the most potent and deeply studied mucosal adjuvants described thus far (44). LT enhances secreted and systemic antibody responses to coadministered soluble or particulate antigens, such as live Salmonella cells, delivered via the oral route (19). In an attempt to enhance flagellin immunogenicity relative to its ability to induce secreted and systemic antibody responses, we orally or nasally immunized BALB/c mice with three doses of live ICB5 strain coadministered with LT R192G , a nontoxic LT derivative with preserved immunomodulatory properties (11).…”
Section: Resultsmentioning
confidence: 99%
“…The discovery of mucosal adjuvants, such as the cholera or heat-labile toxins, has led to a renewed interest in the development of effective oral vaccines based either on acellular formulations or whole live or inactivated microorganisms (11,19,44). In the present work, the incorporation of LT R192G , an LT derivative with reduced toxic effects but preserved adjuvant effects, did not enhance type d flagellin immunogenicity with regard to the production of systemic and secreted antibody responses in mice immunized via mucosal routes with flagellated S. enterica serovar Dublin strains.…”
Section: Discussionmentioning
confidence: 99%
“…Various approaches or a combination of approaches can be examined to overcome the observed partial humoral response with the MASC-13 oral spore vaccine; these approaches include (i) generation of a strain expressing higher levels of PA through utilization of promoters that are much more potent than ␣-amylase (23), (ii) coadministration with mucosal adjuvants (5,25), (iii) engineering the spores with M cells targeting molecules that potentially improve the uptake of the spores by M cells (4,28), and (iv) development of strains which are able to persist longer in phagocytic cells (18).…”
Section: Discussionmentioning
confidence: 99%